1985
DOI: 10.1016/0014-5793(85)80233-7
|View full text |Cite
|
Sign up to set email alerts
|

2‐5A‐dependent endoribonuclease activity and effects of A2'p5'A2'p5'A (2‐5A core) in mouse pancreatic islets

Abstract: Glucose‐stimulated (pro)insulin biosynthesis is markedly inhibited is mouse pancreatic islets incubated with micromolar concentrations of 2‐5A ‘core’, (A2'p5'A2'p5'A). Total protein synthesis was also reduced, but to a lesser extent, while insulin release and total insulin content of the islets was untouched by 2‐5A ‘core’. Evidence is given for the presence of a 2‐5A‐dependent endoribonuclease which mediates these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The cells were cultured for a further 24 h. At near confiuency (-2-4 x 10 G cells per dish), the cells were trypsinized and washed three times in phosphate buffered saline by centrifugation at 4°C, and the cell pellet was homogenized in NP40. Protein concentration was determined as described previously (12). Immunohistochemistry using specific antibodies against insulin or glucagon showed that 63% of aTC3 cells were glucagon positive and none were insulin positive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were cultured for a further 24 h. At near confiuency (-2-4 x 10 G cells per dish), the cells were trypsinized and washed three times in phosphate buffered saline by centrifugation at 4°C, and the cell pellet was homogenized in NP40. Protein concentration was determined as described previously (12). Immunohistochemistry using specific antibodies against insulin or glucagon showed that 63% of aTC3 cells were glucagon positive and none were insulin positive.…”
Section: Methodsmentioning
confidence: 99%
“…that uses ATP in generating 2',5'-oligoadenylates (2',5'A), which in turn serve as substrate for a latent endoribonuclease (RNaseL) (10). The outcome is an inhibition of virus replication and cellular protein synthesis (11,12).…”
mentioning
confidence: 99%
“…Interferon has been shown to inhibit insulin biosynthesis selectively [35]. Furthermore, interferon induces latent 2'-5'oligoadenylate-dependent ribonuclease activity in islets [36]. In the presence of 2'-5'-oligoadenylates, this ribonuclease cleaves mRNA, rRNA and single-stranded viral RNA [37].…”
Section: Light Microscopy Studiesmentioning
confidence: 99%